Bailing out the Kids: New Evidence on Informal Insurance from one Billion Bank Transfers - Asger Lau Andersen; Niels Johannesen; Adam Sheridan (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2020)
We combine transaction-level data from the largest retail bank in Denmark and individual-level data from government registers to study informal insurance within social networks. Accounting for transfers in cash (money transfers) and in kind (cohabitation), we estimate that family and friends jointly replace around 7 cents of the marginal dollar lost within the bottom income decile, but much less at higher income levels. We document that informal insurance covers other adverse events than income losses: expenditure shocks, family ruptures and financial distress. Parents appear to be the key providers of informal insurance with a small amount of insurance coming from siblings and virtually none from grandparents and friends. Replacement rates vary monotonically with parent economic resources.
Keywords: D1; D6; G5; 330; informal insurance; altruism; private transfers; risk sharing